INOVASI TEKNOLOGI AI DI BIDANG ALAT BERAT INDONESIA - Nuhgraha, Yoddy Agung; Anggreini, Novita Lestari; Rohmayani, Dini (Jurnal TEDC, 2025)
The increasing need for efficiency and productivity in the Indonesian heavy equipment sector requires technological innovation to improve performance and reduce operational costs. This article aims to develop and implement Artificial Intelligence (AI) technology in heavy equipment in Indonesia, so that it can improve efficiency and productivity. By using an AI system development approach consisting of several stages, namely data collection, model development, testing, and implementation and also conducting needs analysis and identification of the potential for implementing AI technology in heavy equipment in Indonesia. The results show that AI technology can improve the efficiency and productivity of heavy equipment in Indonesia by reducing operational time and maintenance costs. In addition, AI technology can also improve work safety and reduce the risk of accidents. The conclusion obtained is that AI technology innovation can be an effective solution to improve efficiency and productivity in the Indonesian heavy equipment sector. Therefore, it recommends the application of AI technology to heavy equipment in Indonesia to improve performance and reduce operational costs.